Exploring the Benefits of Artist-in-Residence Programs in Western Australian Schools - Paris, Lisa; O'Neill, Sara (CGScholar: Arts in Society Research Network, 2018)
Where many secondary schools employ specialist art teachers to deliver their education programs in Western Australia, the same cannot be said for primary schools or early childhood centres. In both government and independent sectors across K–6, it is most often the case that visual arts (and the arts generally) are taught by generalist teachers whose preservice training encompassed only minor studies in the arts disciplines. Consequently, there is often a variable quality of art education provided to primary students. As a strategy to support quality arts education outcomes for children in the primary years, Artist-in-Residence (AiR) programs have been shown to have merit. This article presents an overview of an Artist-in-Residence program that has operated in Western Australia since 2007 and provides case studies through which the enrichment and inclusion benefits of artists working in schools are examined.